POTENSI ANTIBAKTERI TANAMAN PARE HUTAN (Momordica balsmina L.) TERHADAP BAKTERI Staphylococcus aureus - Slamet Ifandi; Andi Lindhemutianingrum Siradje; Nur Fatiyah Alhabsyie; Nathasya Anggraini Kabo; Rani Salsabila (Universitas Cokroaminoto Palopo, 2026)
The increasing number of multidrug-resistant (MDR) bacteria due to the widespread use of antibiotics has caused health problems, especially in healthcare facilities, one of which is Staphylococcus aureus bacteria. The purpose of this study was to examine the potential of Bitter Melon (Momordica balsmina L.) leaves as an antibacterial against S. aureus bacteria. This study included a type of laboratory experimental research using a maceration extraction method with 96% ethanol solvent, while the antibacterial test used a well diffusion method. The results of the study on the potential of M. balsmina leaf extract as an antibacterial against S. aureus bacteria obtained an inhibition zone diameter of 11.3 mm and was categorized as strong. The findings in this study indicate that the bitter melon plant has the potential as a source of antibacterial agents, so further investigation is needed.